(untitled) (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
Based on the observation of Bernard Dort and the work of Didier-Georges Gabily, Tadeusz Kantor and Valère Novarina this article discusses the specificity of theater production as critical action capable of providing alternatives to the models produced and promoted by the entertainment industry. To do so, it analyzes phenomenon that locate the stage as a space of emergence, transformation and disappearance of the actor’s body. Upon investigating the exploration of different registers of presence and embodiment of fictions, it also discusses the materialization of the dual incarnation of the actor and the encounter between the actor and his simulacrum as a potential crisis that is capable of deconstructing the media representations of man. Keywords: Contemporary theater. Presences. Simulacrums.